2020
DOI: 10.3389/fimmu.2020.575258
|View full text |Cite
|
Sign up to set email alerts
|

FGFR3 Alterations in the Era of Immunotherapy for Urothelial Bladder Cancer

Abstract: FGFR3 is a prognostic and predictive marker and is a validated therapeutic target in urothelial bladder cancer. Its utility as a marker and target in the context of immunotherapy is incompletely understood. We review the role of FGFR3 in bladder cancer and discuss preclinical and clinical clues of its effectiveness as a patient selection factor and therapeutic target in the era of immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 61 publications
0
79
0
2
Order By: Relevance
“…In patients who received previous ICI (n=22), the confirmed response rate was 59% [ 79 ]. Generally, patients with FGFR3 alterations exhibit lower responses to ICI, although FGFR3 alterations are correlated with a lower grade and stage of NMIBC and a favorable prognosis [ 80 ]. For these reasons, FGFR3 alterations are presumed to predict BCG responses.…”
Section: Emerging Therapies In Bcg-unresponsive Nmibcmentioning
confidence: 99%
“…In patients who received previous ICI (n=22), the confirmed response rate was 59% [ 79 ]. Generally, patients with FGFR3 alterations exhibit lower responses to ICI, although FGFR3 alterations are correlated with a lower grade and stage of NMIBC and a favorable prognosis [ 80 ]. For these reasons, FGFR3 alterations are presumed to predict BCG responses.…”
Section: Emerging Therapies In Bcg-unresponsive Nmibcmentioning
confidence: 99%
“…The microenvironment of a tumor cell showing the dynamics of FGFR3 mutation on tumor cells (phosphorylation of the kinase region leads to activation of AKT, ERK, STAT, and MAPK proteins, which result in target DNA transcription leading to cell proliferation and cell survival), the activation of T cell by tumor cells, and suppression of T cell activation and proliferation by PD-L1 binding with PD-1 much-needed improvements in targeted therapeutics for bladder cancer. The rationale for combining FGFR3targeted therapy with immunotherapy is confirmed in preclinical and correlative literature and animal models suggest potential synergies between these two mechanisms [8]. When attempting to combine two very different therapeutic approaches that target distinct pathways, treatment outcomes can depend on the order and timing in which therapies are administered.…”
Section: Introductionmentioning
confidence: 99%
“…E2F7 contributes to both head and neck cancers and retinal cancers [ 34 ]. Another study found the expression of SNORD88C was similarly altered mRNA splicing for fibroblast growth factor receptor 3 (FGFR3) [ 35 ], which contributes to the progression of multiple cancer types [ 36 , 37 , 38 ]. Interestingly, this mechanism appeared to involve shorter derived sdRNAs from SNORD88C, and as it turns out, this may be a common way that snoRNA expand their influence.…”
Section: The Wider Biological Activities Of Snorna Extend Well Beyond the Ribosomementioning
confidence: 99%